Spatial distribution of beetle attack and its association with mango sudden decline: an investigation using geostatistical tools - Rodrigues-Silva, Nilson; Picanço, Marcelo C.; Pereira, Rogério M.; Galdino, Tarcísio V. da Silva; Silva, Ricardo S. da; Souza, Thadeu C. de (Pest Management Science, 2019)
Ceratocystis fimbriata recognized among the species that induce mango sudden decline (MSD), causes plant death within a short period. The beetles Hypocryphalus mangiferae and Xyleborus affinis (Curculionidae: Scolytinae) are the vectors of MSD. Thorough understanding of the spatial distribution of the pest is crucial to designing control techniques and drawing up sampling plans. This study aimed to identify the beetles and their dispersal pattern in mango trees in MSD‐infected commercial orchards, and the association with the severity of the C. fimbriata infestation. Beetle attacks were observed to be maximal on mango tree trunks revealing severe infestation. From the geostatistical analysis, an aggregated pattern was evident as galleries in the trunks and branches of mango trees. This is the first study to employ geostatic tools on a plant scale in MSD‐infested mango orchards and to study the incidence of beetle attack. The results may prove a highly effective tool for mango growers, with respect to the management of beetles and MSD, as this will facilitate the monitoring of specific sites where the frequency of beetles and MSD is high.
Entomologia
Keywords: Pest management; Mangifera indica; Ceratocystis fimbriata; Mango bark beetle; Ambrosia beetle